Occupational safety and health (OSH) concept towards project performance / Nurul Ayuni Abdul Aziz ... [et al.] - Abdul Aziz, Nurul Ayuni; Mohd Nordin, Rumaizah; Ismail, Zulhabri; Yunus, Julitta; Hashim, Norfashiha (Faculty of Architecture, Planning and Surveying, 2019)
Construction industry is one of the highest incidences after manufacturing industry and also the third biggest contributor to accident cases in Malaysia which making the industry deemed unsafe. The purpose of this research is to identify the causes and effect of construction accident and the impact of occupational safety and health (OSH) concept to project performance. This research is using questionnaire survey method of data collection to 72 respondents from G7 contractors which presenting 75 percent of response rate that involved in the construction of high rise building in Selangor. From the survey, finding shows major factors of construction accident consist of eleven (11) factors that been divided into four (4) main factors (i.e. Human; Worksite; Organization and Management; and External). Moreover, effect of construction accident includes loss ability to work lead to decrease and loss of individual/family income and standard of living, work disruption, delay of work progress, loss of time in project execution, need extra health and safety compliance work, company reputation and image, damages of plant and equipment, property and asset, increase of fine and legal expenses, and loss of productivity. Furthermore, most of the respondents also strongly agree with all statement impact of occupational safety and health (OSH) concept to project performance which include increase workers productivity, reduce rate of construction accident and injuries, increase safety at construction site, improve efficiency, human relations, increase profit, company reputation, business performance, reducing of penalties, insurance premiums and employment costs, quality of product, job satisfaction, morale of the workers, costs saving, and enhancement of project performance. The finding results of this research may contribute in reducing the number of accidents at workplace and assist in designing effective solutions of construction accident.